Arching mechanism of the slab joints in CRTSII slab track under high temperature conditions. (April 2019) - Cai, Xiao-Pei; Luo, Bi-Cheng; Zhong, Yang-Long; Zhang, Yan-Rong; Hou, Bo-Wen
Abstract: China Railway Track System II slab track is widely applied to China high-speed railway. Under the high temperature conditions, it tends to produce different degrees of arch at the joints between prefabricated slabs, which will affect the track irregularity and safe operation of high-speed trains. In this paper, considering the buckling instability of track structure, the arching mechanism of the slab joints was investigated by establishing a 3D finite element model of the CRTSII slab track. Combined with the field investigation, the damage process of joint concrete and its effects on the arching instability were analyzed. The results show: 1) The construction of joint concrete is difficult to control on site, which leads to inferior quality compared to prefabricated slab. The worse quality of joint concrete corresponds to a smaller amplitude of temperature rise causing joints damage and a greater damage area. 2) When the amplitude of temperature rise of the slab is over 37 °C, various damage emerges in the narrow joint and the middle of wide joint, resulting in the eccentric compression. 3) The temperature gradient load will cause the propagation of interface gap between slab and CA mortar layer, which aggravates the arching instability of slab, especially when the height of gap exceeds 1.5 mm. This research is expected to provide guidance for the optimization design, maintenance and damage control of slab track. Highlights: The joint concrete will produce various damage under high temperature conditions. The damage areas mainly occur in the middle of wide joint and narrow joint. Temperature effect and eccentric compression result in the arching instability. The temperature gradient load will aggravate the interface gap and arching instability. Maintain the track structure in time when the gap exceeds 1.5 mm at height.